Iot-Based Cattle Pen Security System Prototype with Wemos - Sasmoko, Dani; Veliyanti, Reni; Ra’ifa, Muhammad Naufal (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2024)
Cattle theft in cow barns frequently occurs in Central Java, Indonesia, highlighting the need for a monitoring system to prevent such thefts. The system developed uses Wemos integrated with a PIR sensor, employing Internet of Things (IoT) methods to detect human movement within the cow barn. A magnetic sensor will be installed on the barn door to provide remote monitoring. The monitoring system activates a buzzer and sends theft data to the cow barn owner from different locations. Testing of this monitoring system was successful, as evidenced by the PIR and magnetic sensors detecting breaches by triggering the buzzer. However, test results indicated that sending data to smartphones requires an internet connection within the barn. Compared to a CCTV system, this setup can deter theft by emitting a loud sound from the buzzer, but it lacks video and photo recording capabilities since it does not include a camera. Based on the design and testing results, it can be concluded that this cattle theft monitoring system has effectively detected suspicious movements in the barn